2022
DOI: 10.3390/jof8080860
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Diversity and Anti-Fungal Resistance of Fungi in Sand of an Urban Beach in Slovenia—Environmental Monitoring with Possible Health Risk Implications

Abstract: Beach safety regulation is based on faecal indicators in water, leaving out sand and fungi, whose presence in both matrices has often been reported. To study the abundance, diversity and possible fluctuations of mycobiota, fungi from sand and seawater were isolated from the Portorož beach (Slovenia) during a 1-year period. Sand analyses yielded 64 species of 43 genera, whereas seawater samples yielded 29 species of 18 genera. Environmental and taxonomical data of fungal communities were analysed using machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Fungal growth slowed when exposed to the maximal protein concentration, and unlike H. werneckii, this may indicate an antagonistic relationship with S. soda . Aspergillus flavus is considered a ubiquitous fungus and mainly isolated from dust, sand, soil, and plant material [ 35 , 48 , 49 ], but it was also isolated from seawater and salterns [ 50 , 51 ]. Its specialization in degrading plant material [ 52 ] likely provides the ability to sustain and even grow at low concentrations of sodin 5 (10 and 20 µg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungal growth slowed when exposed to the maximal protein concentration, and unlike H. werneckii, this may indicate an antagonistic relationship with S. soda . Aspergillus flavus is considered a ubiquitous fungus and mainly isolated from dust, sand, soil, and plant material [ 35 , 48 , 49 ], but it was also isolated from seawater and salterns [ 50 , 51 ]. Its specialization in degrading plant material [ 52 ] likely provides the ability to sustain and even grow at low concentrations of sodin 5 (10 and 20 µg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Its specialization in degrading plant material [ 52 ] likely provides the ability to sustain and even grow at low concentrations of sodin 5 (10 and 20 µg/mL). Aureobasidium melanogenum is associated with freshwater [ 53 ], and is not commonly isolated from saline habitats [ 35 ]. However, as with H. werneckii , A. flavus and T. salinum , also A. melanogenum produce melanin, which is frequently considered an efficient barrier against the defence mechanisms of the host [ 53 , 54 ] and may explain its resistance to sodin 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower abundance of Plectosphaerella was examined in fluoride-induced mice [41,42], Tomentella was positively related to the generation of short-chain fatty acids [43][44][45] and Filobasidium reduced ulcerative colitis [46]; the higher abundance of this genus in the EZ group revealed that concentrated feed #3 promoted sheep health by mediating fungi abundance. The genera of Aphanoascus, Gibberella, Thelonectria and Sebacina are commonly reported in the environment [47][48][49][50]. However, these genera are not pathogenic, but the abundant changes could affect the microbiota function, which eventually affect host status and weight gains.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites produced by extremophiles and extremotolerant fungi are very valuable to produce drugs against cancer cells [ 64 ]. In addition, fungi produce other bioactive metabolites such as mycotoxins, antimycotics [ 65 , 66 , 67 ], immunosuppressants [ 68 ], antifungals [ 69 ], antibacterials [ 70 ], and antivirals [ 71 ]. Even though intensive research has been conducted on fungi-derived natural products and their medicinal properties for more than a century, there are still several fungal metabolites with unknown biological activities that can be considered as new sources of drugs [ 37 ].…”
Section: Introductionmentioning
confidence: 99%